Implementation of Malaysian hand signal codes into applications for the hearing impaired - Diyana, Kamarudin; Yasmin, Hussain (Asya Öğretim Dergisi, 2019)
Hearing-impairment is one of the topics within special education. This disability is one of the factors contributing to difficulty in learning. Unable to effectively communicate is one of the reasons why employment continues to be an elusive goal for people with disabilities. In Malaysia, the Bahasa Melayu subject is compulsory and utilizes Bahasa Melayu Kod Tangan (BMKT), which deaf children have a harder time grasping. They are used to the informal communication, using Bahasa Isyarat Malaysia (BIM). Creating a teaching-aid to translate and back translate between BMKT and BIM would help deaf children adapt better in class, thus improve their communication and learning ability. This research was a preliminary study on getting information from subject matter experts on what they need and what should be implemented into the teaching tool. Two themes were derived from this study, which are students not being able to grasp Bahasa Melayu and technology as a teaching aid. Two subtheme were found for students not being able to grasp Bahasa Melayu are short attention span and BIM as support. A subtheme was found under technology as a teaching aid which is used materials from other sources.